Use of slide latex agglutination test for rapid diagnosis of vaginal candidosis. Issue 3 (June 1987) - Rajakumar, R; Lacey, C J; Evans, E G; Carney, J A
Abstract : A new slide latex agglutination test was compared with microscopy and culture for diagnosing vaginal candidosis in 367 women attending a genitourinary medicine clinic. Vaginal candidosis occurred in 10% of the patients, and 7% had commensal carriage of Candida spp. The slide latex agglutination test was superior to microscopy in immediate diagnosis and was rapid and simple to perform. Of the patients with vaginal candidosis, 72% were detected by slide latex agglutination test compared with 38% by microscopy. The test discriminated well between patients yielding cultures of Candida spp who had symptoms and signs and those who showed commensal carriage.